Enhanced recovery after caesarean delivery versus standard care studies: a systematic review of interventions and outcomes. (August 2020) - Sultan, P.; Sharawi, N.; Blake, L.; Carvalho, B.
Highlights: Studies comparing enhanced recovery after caesarean delivery (ERAC) to control group. 11 peer-reviewed studies; 36 abstracts; 42 ERAC interventions; 90 outcomes reported. GRADE level evidence was low or very low for all outcomes. Most studies showed benefit and none harm, so ERAC adoption is recommended. High-quality studies needed to gain consensus re optimum interventions and outcomes. Abstract: Background: This systematic review aimed to determine whether enhanced recovery after caesarean delivery (ERAC) protocols should be adopted. Methods: We searched four databases and abstracts from meetings for studies comparing ERAC to standard care. We report interventions, outcomes, qualitative impact of ERAC implementation and use GRADE scoring to determine quality of evidence and make recommendations regarding ERAC adoption, based on key outcomes (length of stay, financial savings, satisfaction, re-admission, opioid usage, breastfeeding success and maternal-neonatal bonding). Results: Eleven published studies and 36 abstracts evaluating ERAC were included. Forty-two study interventions (40 in published studies) and 90 outcome measures (60 in published studies) were used. Most studies showed a reduction in hospital stay (6/7 studies) and reduced costs (2/2 studies) with ERAC compared with standard care. Satisfaction was inconsistently reported. Re-admission rates were similar between groups. Two studies showed a reduction and two showed no difference in opioid consumption with ERAC. One study showed improvement and another showed no change in outpatient breastfeeding rates with ERAC. One study showed better inpatient maternal-neonatal bonding. The GRADE level of evidence was low or very low for all outcomes. Conclusions: Studies evaluating ERAC used heterogeneous interventions and outcomes. Although there is currently low- or very low-level evidence supporting all outcomes evaluated, the majority of studies showed some benefits and none reported harm. On balance, we recommend the use of ERAC. Future studies are needed to strengthen ERAC recommendations by standardising interventions and reported outcomes.